Women respond better to biological therapy in Crohn's Disease - Santos,Carlos Henrique Marques dos (2014)
OBJECTIVE: Crohn's disease is in itself a major challenge for those treating inflammatory bowel diseases. Those exhibiting the fistulizing form, particularly perianal fistulas, create even more of a challenge, as there is great difficulty in obtaining disease control even using long-term therapeutic advances made in recent years. We evaluated the difference between the gender of patients under biological treatment for Crohn's Disease and perianal fistula. METHODS: We studied 30 patients with Crohn's Disease with perianal fistula with a mean age of 35 years, from 2000 to 2013. All were naïve to biological agents and received these medications in usual doses and intervals. All were also treated surgically with curettage and placement of seton-stitches prior to the use of biological agents. The results were analyzed statistically by Student's t test, p < 0.05 being considered a significant difference. RESULTS: Among responders, ten were men and nine were women, with no significant difference between genders in this regard. Among non-responders, eight were men and three were women: thus, significantly more men vs. women were non-responders. In general, 55% of men and 75% of women were responders. CONCLUSION: Women exhibited a lower failure rate when exposed to biological treatment for perianal fistula in Crohn's Disease when compared to men.